Evaluation of the quality of irrigation water using the Agriwater software - Bautista, Francisco; Pacheco, Aristeo; Delgado, Carmen (Ecosistemas y Recursos Agropecuarios, 2021)
Since water is an increasingly limited resource, having methods for evaluating its quality is necessary to ensure an adequate and sustainableuse for human consumption, agriculture and industry. The aim of this work was to describe agriwater software for evaluating the quality of irrigation water. The software consisted of the following stages: a) development of a database capable of hosting all the information stored in the software; b) conversion of chemical units; c) indexes calculation; and d) evaluation of performance and efficiency in data processing. The Agriwater software converts measuring units of ions to mg L-1, meq L-1 and mmol L-1, calculating the following water quality indexes: sodium absorption ratio, effective salinity, potential salinity and chloride toxicity. The result is Agriwater software, a professional tool that can handle, analyze and evaluate thousands of data in seconds in an intuitive and simple way.
Keywords: Salinity; Sodicity; types water; Effective salinity; Potential salinity